1995
DOI: 10.1093/ajcp/103.1.82
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Involvement in Anaplastic Large Cell Lymphoma:Immunohistochemical Detection of Minimal Disease and Its Prognostic Significance

Abstract: Bone marrow involvement by anaplastic large cell anaplastic large cell (ALC) lymphoma can be difficult to detect on routine morphologic examination alone. In a series of 42 patients with ALC lymphoma, the authors analyzed: (1) the usefulness of a limited panel of monoclonal antibodies directed against CD30 (Ber-H2, HRS4) and epithelial marrow involvement on routinely processed biopsy specimens; and (2) the prognostic significance of bone marrow involvement as detected on both morphologic and immunohistochemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(61 citation statements)
references
References 32 publications
3
57
0
1
Order By: Relevance
“…Bone marrow involvement is relatively common in ALCL, but may be easily missed in routine trephine sections or aspirate smears (58). The neoplastic cells usually infiltrate as single cells, and are most readily identified with stains for CD30, EMA, or ALK.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Bone marrow involvement is relatively common in ALCL, but may be easily missed in routine trephine sections or aspirate smears (58). The neoplastic cells usually infiltrate as single cells, and are most readily identified with stains for CD30, EMA, or ALK.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Fraga et al (1995) reported that in a case series (n542) of anaplastic large cell lymphoma, routine histology detected marrow involvement in 17% cases. Routine IHC analysis using CD30 detected occult disease in a further 23% cases (Fraga et al 1995). We found BM involvement on routine histology in 19.2%, with a more modest 11.1% rate of occult involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Scattered malignant cells may be missed quite easily on routine histology (Fraga et al 1995) but be more easily discernible on IHC analysis. Such cases were classified positive when numbers of B cells were increased compared with controls.…”
Section: Bm Histologymentioning
confidence: 99%
“…5,9,10,[12][13][14]19 In a report analyzing bone marrow involvement in ALCL, the incidence was 17% with histology only, whereas 40% of cases were found to be positive when immunohistochemistry was combined. 20 Circulating tumor cells or involvement of the gastrointestinal tract or central nervous system (CNS) are rarely detected at diagnosis. 5,9,10 CNS relapse occurs in a small subset of patients.…”
Section: Clinical Featuresmentioning
confidence: 99%